Proceso de atención nutricional en paciente masculino de 88 años con enfermedad pulmonar obstructivas crónica. - Bajaña Valle, Luisa Johily (2022)
Nutritional assessment and therapy are a fundamental part of the comprehensive management of patients with chronic obstructive pulmonary disease, taking into account the high incidence of malnutrition and its clinical complications, the objective as a nutritionist is to reduce, prevent and treat malnutrition problems by adapting the dietary management of the patient's problems considering aspects such as age, sex and socioeconomic level; the adaptation of the food plan by oral route and the energy requirements are the main characteristics that direct us to an adequate nutritional treatment. In this clinical case study, a nutritional care process was carried out on an 88-year-old patient with chronic obstructive pulmonary disease, where anthropometric aspects that reflected low weight were evaluated; biochemical: mild anemia; clinical: dry skin and brittle hair and dieteic bad eating habits. He was provided with a hypercaloric and hyperprotein food plan divided into 5 meals a day, soft consistency where they included easily digestible foods and proteins of high biological value, nutritional supplementation was included twice a day, in order to improve the nutritional status of his patient. You see improves the patient's quality of life through proper nutritional intervention throughout the patient's treatment phase. Through the nutritional intervention plan that was adapted to the patient, positive results were obtained at the anthropometric, biochemical, clinical and dietary levels, improving the health condition of the patient with Chronic Obstructive Pulmonary Disease.